Party decline or social transformation? Economic, institutional and sociological change and the rise of anti-political-establishment parties in Western Europe. Issue 4 (29th November 2020) - Casal Bértoa, Fernando; Rama, José
Abstract: The rise in support for anti-political-establishment parties (APEp), especially since the beginning of the 2008 Great Recession, has put democracy in peril. Some scholars have warned us about the negative implications the recent rise of APEp might have for the development of democracy in Western Europe. For that reason, it is important we begin to understand what generates APEp's electoral success. Drawing on a new comparative dataset that examines all Western European democracies from 1849 until 2017, the current article attempts to provide an explanation. In particular, our analyses examine three alternative explanations put forward by the literature: economic, institutional, and sociological. Our results show that it is not economic performance but both institutional and sociological change which together can help to understand the current wave of support for APEp.